THE GLYMPHATIC SYSTEM AND ITS POTENTIAL IMPLICATIONS FOR NEURODEGENERATIVE DISORDERS: A NARRATIVE REVIEW (Conferencea, 2024)
The Glymphatic system, proposed by Jeffrey Iliff and Maiken Nedergaard in 2012, refers to a macroscopic waste clearance system in the brain that resembles the peripheral lymphatic system. Numerous studies indicate that the Glymphatic system significantly influences the distribution of various substances in the brain, including its primary waste clearance function and the transport of nutrients like glucose, treatment substances and glial calcium signaling. Three components that make up the Glymphatic system: a trans-parenchymal component that depends on astroglial water transport, a paravenous ISF clearance pathway, and a para-arterial CSF influx pathway. The Glymphatic system has many unexplored aspects, particularly regarding its driving forces and its connection to sleep and neurodegenerative disorders. The interaction between the Glymphatic system and inflammation appears to be cyclical and potentially synergistic. The researches indicate that inflammation aggravates Glymphatic system dysfunction. The impaired Glymphatic system exacerbates the neurodegenerative disorders progression and neurodegenerative disorders progression promotes inflammation. Both inflammation and Glymphatic system dysfunction are the common pathological features in AD, PD, and other neurodegenerative disorders. The present researches about Glymphatic function could lead to new treatments that will likely be most effective when used early in disease onset. Way to assess Glymphatic flow with magnetic resonance imaging is currently under development as clinical diagnostic tool.